Assessing the Effectiveness of the Crediting of the Agro-Industrial Complex, as the Determining Sector of International Trade, by Region - Sergienko Olena A.; Gula Alla S. (Problemi Ekonomiki, 2018)
In the article, to assess the efficiency of the crediting of the agro-industrial complex (AIC), as the determining sector of international trade, by region, a methodological approach to assessing and analyzing the determination of levels of performance and crediting of AIC is proposed. Unlike the existing approaches, the one presented in the article is based on the results of cluster analysis methods and spatial multielement matrices of conformity of the investigated components (by level of performance of the AIC and level of crediting of the AIC), which is the basis for studying the effectiveness of the influence of crediting on its performance by the formed groups of regions with the help of econometric tools as well as for determining the features of the investigated processes in the regions and allows to assess the effectiveness of using credit resources when choosing levers of regulatory influence. The constructed models for assessing economic efficiency of the crediting of agribusinesses enables determining the impact of using credit resources aimed at increasing the effectiveness of their activities, as well as the problems of their crediting in the regional context. The models for assessing the impact of crediting volumes on the level of production and net profit make it possible to predict the effectiveness of raising funds and justify the development of the crediting of agribusinesses in regions of the country. It is proved that the strategic line for the development of the crediting of agricultural enterprises in regions according to the level of agricultural development is the transition from the predominantly basic support for the crediting of agribusinesses to the crediting and financing their specific projects, which will ensure the most effective activity at all management levels based on the determined areas of development of crediting with regard to the level of creditworthiness of agribusinesses.